(943) The Integration of the State Insurance into the Economic System of the German Democratic Republic دمج التأمين الحكومى في النظام الاقتصادي لجمهورية ألمانيا الديمقراطية - Bader (The Institute of National Planning, 2024)
The economic system of socialism is a system of the conscious use of the economic laws of socialism by the State under the leading of the working class. This includes the active participation of all workmen in the framework of their social life. Securing a high and continuous increase of work productivity is an objective that is also included in our system of comprehensive socialist planning in the GDR. According to this idea remarkable changes have been carried out step by step in all spheres of the national economy.